P158 THE ENGRAFTMENT OF THE GUT MICROBIOTA FROM CROHN'S DISEASE PATIENTS IS NOT NECESSARILY 'STABLE' BY DAY 28 IN MICE PRONE TO CROHN'S DISEASE-LIKE ILEITIS. (7th February 2019) - Basson, Abigail R; Gomez-Nguyen, Adrian; LaSalla, Alexandria; Ezeji, Jessica C; Erkkila, Hailey L; Rodriguez-Palacios, Alexander; Cominelli, Fabio
Abstract: Background: The majority of fecal microbiota transplantation (FMT) peer-review publications suggest that 28 days is sufficient to assess the effect of human microbes because studies in healthy mice (C57BL/6J) indicate that transplanted human gut microbiome is 'stable'. On the contrary, we present data that illustrates that microbiome stability is a relative concept, that vary across donors and that their functional effect on intestinal health should only be assessed beyond such period to cover innate and adaptive immunity relevant in chronic inflammatory diseases, including Crohn's Disease. Methods: Sixty-day FMT experiments (and culturomics) were conducted in triplicate (9 human donors, 96 germ-free mice, 403 samples) using a genetic mouse line affected with chronic cobblestone Crohn' Disease-like ileitis (SAMP1/YitFC; SAMP). To verify 16S microbiome time-series donor-dependent dynamics, we employed as 'gold standard' the isolation of cultivable members of Enterobacteriaceae using McConkey agar and a novel "Parallel Lanes Plating" method for fecal samples collected from recipient mice on days 1, 7, 28 & 60 (representative of periods of early innate and long-term adaptive immunity). Variability of species over time was assessed using colony forming unit (CFU) enumeration and single colony Sanger sequencing of the 16s rRNA gene V4 region. Results: Time-series analysis of 16S data among FMT recipient mice showed significant changes in patterns of bacterial Family absolute read count abundance occurring after day 28. For instance, Ruminococcaceae increased while Enterobacteriaceae decreased for Crohn's Disease donors, while a 'crescendo-decrescendo' oscillation pattern was evident for Enterobacteriaceae in 'Healthy' donors. Despite significant differences in the magnitude of taxon absolute abundance between recipient groups, temporal dispersion showed that patterns of variability were consistent. CFU data (48h aerobic/anaerobic incubation) confirmed 16S sequencing data and late stabilization of microbiome (e.g., Enterobacteriaceae decreasing 1000-fold over time (2-3 logs). Speciation confirmed presence of Escherichia marmotae, but also supported the ability to infer positive presence of taxon not detected at the Order level by 16S. Conclusion: Collectively our data indicates that the dynamic engraftment of the human gut microbiota in mice can be verified by culture methods and is not necessarily stable by day 28 as often used in IBD experiments, but rather may be variable until day 60 (permits innate and adaptive response to the engrafted microbiome), depending on which donor was sampled.